Pendampingan Pengembangan Digital Branding Pada UMKM Fiya Cake di Desa Sumberbendo - Bernika Maura Alfionita; Ardiansyah Putra; Nabella Rosa Anggun Pitaloka; Fariq Hisba Ash-Shiddiqy; Ainan Salsabila; Nurkholis Majid (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
The Coordinating Ministry for the Economy of the Republic of Indonesia (2022) reports that Micro, Small and Medium Enterprises (MSMEs) are important players in the Indonesian economy, accounting for 99% of all economic sectors. MSMEs contribute 60.5% to GDP (Gross Domestic Product) and are able to absorb 96.9% of the national workforce (Sakum & Ismamudi, 2022). But on the one hand, MSMEs experience many internal and external obstacles so they cannot maximize their business, one of which is UMKM Fiya Cake which has problems in applying visual branding, namely not having a business identity in its application. Therefore, the solution that will be provided as an effort to introduce Fiya Cake's business products is to design and create a business identity in the form of a logo, banner, and also create an NIB. The method used in this activity is the mentoring method which begins with a survey, planning, implementation, and evaluation. The results to be achieved from this service activity are the creation of branding as a form of business identity so that it will be easy to remember by the wider community.